From Analytic Philosophy to an Ampler and More Flexible Pragmatism: - Muhammad Asghari; Susan Haack (Journal of Philosophical Investigations, 2020)

(untitled)
In this interview, which took place in July 2020, Muhammad Asghari, an associate professor in the Department of Philosophy at the University of Tabriz, asked eleven questions (via email ) to Professor Susan Haack, a distinguished professor of philosophy at the University of Miami. This American philosopher eagerly and patiently emailed me the answers to the questions. The questions in this interview are mainly about analytic philosophy and pragmatist philosophy.This interview was conducted via personal email between me and Professor Susan Haack in July 2020. This interview, which Professor Hawk eagerly accepted, includes eleven questions about her biography and roles of various philosophers in her thought and finally about the influence of the philosophy of pragmatism on her thought. Of course, it goes without saying that the Haack's book Philosophy of Logic in Iran has been translated into Persian and he has published two articles in the quarterly journal of Philosophical Investigations (University of Tabriz) and I also have translated one of her articles into Persian. What was most interesting to me was the influence of pragmatism on Haack's thought that Charles Sanders Pierce, among classical American pragmatists, had as much influence on this philosopher's thought as John Dewey had in Rorty's thought. Here I thank Professor Susan Haack for answering my questions patiently and eagerly.